Impact of Daylighting on Visual Comfort and on the Biological Clock for Teleworkers in Residential Buildings - Ignacio Acosta; Miguel Ángel Campano; Laura Bellia; Francesca Fragliasso; Francesca Diglio; Pedro Bustamante (Buildings, 2023)
The current socio-economic scenario has promoted telecommuting at home for a significant number of workers, mainly due to the sanitary situation experienced and the improvement in communication technologies. However, the work context at home is often not suitable for teleworking since the environmental conditions are not usually adequate for good performance and the wellness of workers. The received light, both in quantity and in spectrum, affects the visual comfort and performance of the worker through the regulation of the circadian stimulus. Accordingly, the objective of the present study is to ascertain the influence of natural daylight on the performance and health of teleworkers, considering a room at home analyzed in three different locations, two orientations, two-time schedules, and two window shapes. The impact of natural light on health was assessed using the Circadian Stimulus Autonomy (CSA) produced by daylight during the morning, while the illuminance requirement was defined in accordance with the Daylight Autonomy (DA). The results obtained were contrasted with a real test cell under real daylight conditions. The conclusions of this study serve to determine the suitable windowed areas of the analyzed room where teleworkers obtain the appropriate lighting performance and well-being.